Effect of Sodium Tripolyphosphate (STPP) to Physicochemical and Sensory Characteristics of Turkey Nuggets Derived from White and Dark Turkey Meats - Sutarjo Surjoseputro; Petrus Sri Naryanto; Meliawati Fatoni (Indonesian Food and Nutrition Progress, 2004)
Turkey meat is a well-known foodstuff and source of protein in the United States, while in Indonesia turkey meat has not yet optimally processed as a foodstuff. The advantages of turkey meat are: has low calorie, high protein than other poultry meats, and good source of vitamin and mineral. Contrary to chicken meat, turkey meat has low fat content and high collagen, and therefore makes the meat very tough. This research was using two kinds of meat, the white meat (the breast) and the dark meat (the leg) for nuggets. These two parts have different characteristics, physically as well as chemically. This research was designed in a Nested Randomized Design where STPP were subjected to each part of turkey meat in four levels, 0.0, 0.2, 0.4 and 6.0%, respectively. The objective of this research was to find the most effectiveness of STPP and the most acceptable turkey nuggets. The results of this research were that STPP 0.6% was the best choice for white meat and STPP 0.4% was the best choice of dark meat.